2021
DOI: 10.2147/jir.s299557
|View full text |Cite
|
Sign up to set email alerts
|

Isovitexin Depresses Osteoarthritis Progression via the Nrf2/NF-κB Pathway: An in vitro Study

Abstract: Purpose Osteoarthritis (OA) is a multifactorial joint disease and inflammatory processes contribute to joint destruction. Isovitexin (IVX) is a flavone component found in passion flower, Cannabis and, and the palm that is known for its anti-inflammatory properties. Materials and Methods This study investigated in vitro the role and underlying mechanism used by IVX in its regulation of OA development. Effects of IVX on the viability of chondrocytes were measured by CCK-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Previous study indicated that isovitexin suppresses NF-κB pathway in osteoarthritis (Hu et al. 2021 ). In our study, isovitexin can significantly inhibit the expression of TLR4 protein in the synovium of rats with acute gout, and can also significantly antagonize the expression of NF-κB p65 in the synovium.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous study indicated that isovitexin suppresses NF-κB pathway in osteoarthritis (Hu et al. 2021 ). In our study, isovitexin can significantly inhibit the expression of TLR4 protein in the synovium of rats with acute gout, and can also significantly antagonize the expression of NF-κB p65 in the synovium.…”
Section: Discussionmentioning
confidence: 95%
“…Recent results indicate that isovitexin could suppress osteoarthritis progression (Hu et al. 2021 ). Isovitexin has the advantages of easy extraction, high content and stable performance, which is expected to become an alternative drug for biodiversity (Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with previous studies [ 48 , 49 ], excessive oxidative stress induced by IL-1β in this study significantly activated Nrf2 signaling in primary chondrocytes. Most published studies suggested Nrf2 signaling activation relates with its protective ability to inflammatory responses [ 50 52 ]. Nevertheless, we found that CDs inhibited the activation of Nrf2 signaling and HO-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Moracin ( 3 , isolated from Cortex Mori. Radicis, Moraceae ), Isovitexin ( 4 , isolated from the passion flower ( Passiflora edulis Sims, Passifloraceae ), Cannabis ( Cannabis sativa L., Moraceae ), and palm ( Elaeis guineensis Jacq., Arecaceae )), Eriodictyol ( 5 , isolated from citrus fruits ( Citrus reticulata Blanco, Rutaceae )), Licochalcone A (Lico A, 6 , isolated from the licorice root ( Glycyrrhiza uralensis Fisch., Leguminosae )), and Epigallocatechin-3-O-gallate (EGCG, 7 , isolated from tea leaves) exhibit similar effects against inflammatory responses by activating the NRF2 signaling in OA chondrocytes ( Jia et al, 2017 ; Wang Y. et al, 2018 ; Zhou et al, 2020 ; Hu et al, 2021 ; Zhu et al, 2022a ) ( Tables 1 , 2 ). In addition, EGCG (100 μM) also suppresses the JNK/MAPK signaling and inhibits inflammatory responses in IL-1β-treated human chondrocytes ( Akhtar and Haqqi, 2011 ).…”
Section: The Interaction Between Oxidative Stress and Oamentioning
confidence: 99%